Sextus Empiricus and the Differences between Pyrrhonism and the Philosophy of the Academics: A Translation of Outlines of Pyrrhonism 1.220-235 - Huguenin, Rafael; Brito, Rodrigo Pinto de (Revista Archai, 2019)
This paper consists in the presentation of the first version of the Greek/Portuguese translation of Sextus Empiricus’ Outlines of Pyrrhonism 1.220-235, passage where Sextus traces a comparison between the Pyrrhonism and the Academic philosophy.